2001
DOI: 10.1021/ie0007825
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Heating Behavior of Supported MoS2 and Pt Catalysts

Abstract: The temperature of supported MoS 2 and Pt catalysts was measured during microwave heating at constant input power by inserting a thermocouple into the center of the catalyst bed immediately after the microwave power had been turned off at the end of progressively longer heating times. Thermal runaway was observed with MoS 2 /Al 2 O 3 and Pt/Al 2 O 3 at temperatures in the range 285-300°C when the power absorbed rose with temperature at a rate greater than that at which heat is lost by cooling. This condition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…It can be seen that, in general, the absorbed power increased with temperature rising and the increase in power tended to be smaller at higher temperatures indicating an increase in microwave heating efficiency. This is in agreement with the previous study where the dielectric loss of the catalyst generally increased with increasing temperature [22,23].…”
Section: Microwave Power Absorptionsupporting
confidence: 93%
“…It can be seen that, in general, the absorbed power increased with temperature rising and the increase in power tended to be smaller at higher temperatures indicating an increase in microwave heating efficiency. This is in agreement with the previous study where the dielectric loss of the catalyst generally increased with increasing temperature [22,23].…”
Section: Microwave Power Absorptionsupporting
confidence: 93%
“…In work with an 8% MoS 2 /alumina catalyst [21], it was found that the fraction of the input power that was absorbed by the catalyst increased from 0.13 at 18 • C to 0.25 at 350 • C. The higher values reported here must be due to the greater loading of molybdenum sulfide (30%). This material has an effective dielectric loss factor of 0.85 at 200 • C [22], compared to 0.025 for alumina, and must be responsible for the major part of the heating.…”
Section: Microwave Power As a Function Of The Temperature Of Catalystmentioning
confidence: 56%
“…The much lower temperature measured when microwave radiation is used must arise from temperature gradients within the catalyst. These temperature gradients will cause localised heating of the gaseous reactants because of the high rate of heat transfer between the internal surface of the catalyst and the gas phase, as investigated in our earlier work [32]. Fig.…”
Section: Reaction Of Methane In Absence Of Oxygen Without Catalystmentioning
confidence: 87%
“…This indicated an increase in microwave heating efficiency at higher temperatures, and may be attributed to the increase in the dielectric loss of the catalyst with increasing temperature [32].…”
Section: Microwave Power As a Function Of The Temperature Of Catalystmentioning
confidence: 94%